Analysis of Characteristics, Fatty Acid Composition, Antioxidant Activity, and Beta-sitosterol of Moringa (Moringa oleifera Lam) Oil from Three Different Regions in Indonesia - Chasanah, Uswatun; Yuliani, Sapto; Sugihartini, Nining (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2025)
Moringa oil offers a range of health, nutritional, and cosmetic benefits. However, its characteristics can vary greatly depending on its geographical origin. This study aimed to compare the physicochemical properties, fatty acid composition, antioxidant activity, and beta-sitosterol content of moringa oil obtained from three regions in Indonesia: Central Java, Central Sulawesi, and East Nusa Tenggara. The physicochemical properties examined include organoleptic, specific gravity, viscosity, refractive index, iodine value, acid value, saponification value, and peroxide value. Furthermore, the fatty acid composition was analyzed using gas chromatography with flame ionization detection (GC-FID), antioxidant activity was evaluated by the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, and beta-sitosterol content was measured by thin-layer chromatography (TLC). Physical attributes, such as viscosity and specific gravity, do not exhibit significant differences between the regions. At the same time, chemical parameters, which include iodine value, acid value, and saponification value, show considerable variations. Fatty acid profiles revealed that oils from Central Sulawesi and East Nusa Tenggara have high oleic acid and low polyunsaturated fat content, providing better oxidative stability and longer shelf life. In contrast, Central Java oil showed higher levels of linoleic and behenic acids, making it more suitable for sensitive skin and hair care applications. Central Java oil exhibits the highest antioxidant activity, whereas Central Sulawesi oil contains the highest concentration of beta-sitosterol, suggesting a more significant potential as an anti-inflammatory agent. These findings highlight the influence of regional origin on the quality of moringa oil, presenting exciting opportunities for further research in this field.